2016
DOI: 10.1192/bjp.bp.114.150961
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of flexible cognitive–behavioural therapy and medical treatment, including antidepressants on post-traumatic stress disorder and depression in traumatised refugees: pragmatic randomised controlled clinical trial

Abstract: In a pragmatic clinical setting, there was no effect of flexible CBT and antidepressants on PTSD, and there was a small-to-moderate effect of antidepressants and psychoeducation on depression in traumatised refugees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 38 publications
5
86
0
Order By: Relevance
“…A previous randomized clinical trial of eye movement desensitization and reprocessing vs fluoxetine showed no differences 12 weeks after treatment, 12 and a study comparing a hybrid traumafocused exposure-based acceptance and commitment therapy and medical management (sertraline supplemented with a sleep aid), or their combination, showed no significant differences after treatment. 9 Finally, prolonged exposure therapy resulted in statistically higher rates of remission of PTSD compared with paroxetine, but the combination of prolonged exposure therapy and paroxetine did not differentiate from either alone. 11 Importantly, this study was designed to deliver sertraline and prolonged exposure therapy plus sertraline under matched conditions that included rigorous training and ongoing supervision of psychotherapists and pharmacotherapists.…”
Section: Discussionmentioning
confidence: 92%
“…A previous randomized clinical trial of eye movement desensitization and reprocessing vs fluoxetine showed no differences 12 weeks after treatment, 12 and a study comparing a hybrid traumafocused exposure-based acceptance and commitment therapy and medical management (sertraline supplemented with a sleep aid), or their combination, showed no significant differences after treatment. 9 Finally, prolonged exposure therapy resulted in statistically higher rates of remission of PTSD compared with paroxetine, but the combination of prolonged exposure therapy and paroxetine did not differentiate from either alone. 11 Importantly, this study was designed to deliver sertraline and prolonged exposure therapy plus sertraline under matched conditions that included rigorous training and ongoing supervision of psychotherapists and pharmacotherapists.…”
Section: Discussionmentioning
confidence: 92%
“…From a clinical perspective, it is possible that the assessment of symptoms among refugees has been excessively constrained to those of core PTSD. In that regard, it is notable that some studies undertaken among refugees in resettlement countries have documented a poor symptom response to conventional treatments for PTSD and depression (49, 50). The chronicity and complexity of the cases that receive treatment at specialized refugee-mental health services in these settings raise important questions whether the difficulties encountered in providing effective treatment relate in part to a failure to acknowledge the extent of the TS response which extends beyond core PTSD to encompass symptoms defined in ICD-11 as C-PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, two published papers describing the trauma-affected refugees at the time of referral to CTP, from the same period find that the mean number of years since the first trauma was 22 years and the mean number of years with mental health problems as recalled by the patients were 14.7 years, similar to the time of arrival in Denmark. From these studies we expect that the number of years with mental health problems is substantial when admitted to treatment [51, 52]. …”
Section: Discussionmentioning
confidence: 99%